Produção de etanol utilizando cascas de banana e de laranja por co-fermentação de Zymomonas mobilis e Pichia stipitis - Coimbra, Michelle Cardoso [UNESP] (2015)
The generation of ethanol from lignocellulosic waste, such as fruit crops, can be an alternative and renewable energy source. Brazil is one of the largest producers of tropical fruits in the world, especially orange and banana. As a result, it is able to generate large amounts of waste that may be used as biomass, which once hydrolyzed, releases pentoses and hexoses. In order to get a higher ethanol yield, the use of co-cultures which metabolize both pentose and hexose becomes quite interesting. In this context, the objective of this work was to study the hydrolysis effect of banana and orange peels for ethanol production by co-cultures of Zymomonas mobilis and Pichia stipitis. The acid hydrolysis was performed with 5% sulfuric acid and 15 min in autoclave; for the enzymatic hydrolysis was used a commercial kit supplied by Novozymes, in reaction at 50°C for 36 h. After the hydrolysis the medium was detoxified with activated carbon. The effects of fermentation by Z. mobilis monoculture and Z. mobilis and P. stipitis co-cultures, pH, agitation and the initial amount of sugars in the middle were evaluated. The sequential acid and enzymatic hydrolysis released 64.97 and 134.75 g/L of total sugars from banana peels and 101.30 and 176.70 g/L of total sugars from orange peels, respectively. The detoxification of the hydrolysate resulted in a removal of 58% to 93% of phenol and 1.7% to 4% of the total sugars. In Erlenmeyer fermentations with synthetic medium, the largest cell growth and maximum ethanol production were 1.52 and 11.29 g/L for Z. mobilis monoculture, and 8.00 and 77.02 g/L for the co-culture, respectively. In the medium with banana peels, these responses were 1.87 and 4.16 g/L for monoculture, and 15.19 and 23.92 g/L for the co-culture, respectively. To the medium with orange peels, the same responses were 0.39 and 1.85 g/L for monoculture and 6.73 and 11.36 g/L for the co-culture, respectively. For all evaluated media, the Z. ...